Culturazi - Culturazi (Canberra, A.C.T.) (Canberra, A.C.T. : Culturazi, 2004)
"Culturazi is a loose collective of artists, writers and musicians operating from Canberra, Australia." The website contains news, activities, images and blog.
Title from title screen (viewed on 31 May 2010)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.culturazi.com
Selected for archiving
Keywords: Arts -- Australian Capital Territory; Authors -- Australian Capital Territory; Musicians -- Australian Capital Territory